Remedies for default in Islamic banking: home and car financing - Hassan, Rusni; Othman, Ahmad Azam; Mokhtar, Norlizah (Sweet & Maxwell Asia/Thomson Reuters Malaysia, 2018)
This book contains an in-depth, focused and up-to-date discussion on the practical application of the remedies that are available to banks and financial institutions following breach or default by customers of Islamic home and car financing facilities, namely bai` bithaman ajil, ijarah and musyarakah mutanaqisah financing, which are the three commonly preferred Islamic banking facilities for home and car financing in Malaysia. The issues that commonly arise in Islamic financing practice are carefully considered to give clear and instructive guidance on how particular remedies may be successfully sought for each type of financing.